METHODOLOGICAL BASES OF USING OF SPECIAL KNOWLEDGE IN CIVIL AND ARBITRATION PROCEEDINGS - M. V. Zhizhina (Теория и практика судебной экспертизы)
The scienti!c and methodological foundations of drawing on expertise in civil andarbitration proceedings in the present conditions, the necessity of creation of technicaland tactical security forensic evidence with special knowledge in civil (arbitration)proceedings are discussed in this article. The author also focuses on the most problematicissues: the need to adjust the notion of "special knowledge" and amending the existinglegislation, verifying the competence of experts and specialists in connection with thecases in the judicial practice of asking questions, border legal, and so on.